Assessing fintech behavioral adoption to enhance financial readiness for retirement among malaysian gig workers: A conceptual framework - Mohd Nur Fadzly, Basar; Noraina Mazuin, Sapuan; Azim Azuan, Osman (Academic Inspired Network, 2026)
The rapid growth of gig economy has sparked worry about gig workers ability to retire with dignified financial wellbeing especially when employer-based benefitsare absent and their incomes are inconsistent. Nowadays, financial technology (fintech)has become increasingly pertinent in financial management, offering everyone including gig workers new method to monitor their income, schedule automatic savings and to contribute voluntarily to their personal retirement fund. Yet, the studiesabout how their willingness to adopt fintechmay influence their Financial Readiness for Retirement (FRR)are still limited. This paper proposes a conceptual framework that associatesFintech Behavioral Adoption (FBA) to FRR, grounded inthe Net Valence Framework (NVF). In this model, FBA is shaped by how gig workers weigh the benefits of fintechsuch as easy to use, lower costs, and better financial oversightagainst the risks they associate with it, including privacy concerns and possible financial loss. When perceived benefits outweigh perceived risks, gig workers are more likely to adoptfintech to manage their finance and subsequently improve their FRR. The framework recommends a new insightfor policymakers, financial institutionsand platformproviders seeking to design digital financial toolsthat usefulforthis vulnerable groups for preparing for their retirement age.